Scientific theft (Reasons, avoiding it) "Sociological Analytical Study" - الجوراني, نبال (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The presented research deals with the phenomenon of scientific theft, this phenomenon which has become widespread in society. The tools of sociological analysis have been applied to do research on and understand this phenomenon, as it is one of the mistakes that many students and researchers make. (Errors) have occurred deliberately or unintentionally due to lack of knowledge of the correct methodologies for scientific research, errors like (documentation, citation, summary, rewording ...). Therefore, the main purpose of the research is to shed light on this phenomenon in all its dimensions, so we can collect enough data to propose the best methods and the possible ways to help the student and researcher to avoid Falling into scientific theft as much as possible.